2008
DOI: 10.1038/pcan.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

Deletion at chromosome arms 6q16–22 and 10q22.3–23.1 associated with initiation of prostate cancer

Abstract: Loss of heterozygosity (LOH) at 6q16-22 and 10q22.3-23.1 is common chromosomal alteration in advanced prostate cancer and suggests that one or more tumor suppressor genes may lie within these chromosome arms. However, the genetic changes in early stage prostate cancer and premalignant lesions remain to be investigated. We used 11 informative microsatellite markers at 6q16-22 and 10q22.3-23.1 in Japanese patients to compare the frequency of LOH in 53 lesions of high-grade prostatic intraepithelial neoplasia (HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…8q24.21, leukemia/lymphoma (66,67); chr. 10q22.3, non-small cell lung cancer, prostate cancer (68,69); chr. 11p.15.4-5, Beckwith-Wiedemann cancer predisposition syndrome, T lymphoid leukemia (7072); chr.…”
Section: Discussionmentioning
confidence: 99%
“…8q24.21, leukemia/lymphoma (66,67); chr. 10q22.3, non-small cell lung cancer, prostate cancer (68,69); chr. 11p.15.4-5, Beckwith-Wiedemann cancer predisposition syndrome, T lymphoid leukemia (7072); chr.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, WDR76 has a large interaction network, including HELLS and PARP1 30 , supporting synthetically lethal interaction with PARP inhibition. RNASEH2B and MMS22L are located on chromosomes 13q14 and 6q16, respectively, which have long been recognized as two frequently deleted regions in PCa [31][32][33][34][35][36][37] . While loss of RNASEH2B might cause ribonucleotide excision repair deficiency and PARP-trapping lesions as previously reported 13 , we recently reported that co-loss of RB1, a closely located tumor suppressor gene, was antagonistic in PCa cells 38 .…”
Section: Validation Of Negatively Selected Genes Related To Parpi Sen...mentioning
confidence: 99%
“…RNASEH2B and MMS22L are located on chromosomes 13q14 and 6q16, respectively, which are two genomic regions frequently deleted in PCa [29][30][31][32][33][34][35] . While loss of RNASEH2B might cause ribonucleotide excision repair deficiency and PARP-trapping lesions as previously reported 13 , we recently reported that co-loss of RB1, a closely located tumor suppressor gene, was antagonistic in PCa cells 36 .…”
Section: Validation Of Negatively Selected Genes Related To Parpi Sen...mentioning
confidence: 99%